2021
DOI: 10.1109/access.2021.3077498
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Networks Based Online Behavioural Malware Detection Techniques for Cloud Infrastructure

Abstract: Several organizations are utilizing cloud technologies and resources to run a range of applications. These services help businesses save on hardware management, scalability and maintainability concerns of underlying infrastructure. Key cloud service providers (CSPs) like Amazon, Microsoft and Google offer Infrastructure as a Service (IaaS) to meet the growing demand of such enterprises. This increased utilization of cloud platforms has made it an attractive target to the attackers, thereby, making the security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Kimmel et al [46] used an RNN model to improve the security of cloud services, particularly against cloud malware. Cloud malware is software that is widely used to attack VMs hosted on cloud IaaS.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimmel et al [46] used an RNN model to improve the security of cloud services, particularly against cloud malware. Cloud malware is software that is widely used to attack VMs hosted on cloud IaaS.…”
Section: Related Workmentioning
confidence: 99%
“…The average accuracy of the HUDH scheme was determined with a maximum 5000 generated threats and compared to state-of-the-art algorithms: SA-DECC [42], SE-AC [43], BRNN-L, and IDTRE [46,49]. Based on the results (Figure 9), we found that the proposed HUDH method produced an average accuracy of 99.48%; the average accuracies of BRNN-L, IDTRE, SE-AC, and SA-DECC were 98.51%, 97.82%, 98.14%, and 97.79%, respectively, showing that the proposed scheme has higher average accuracy.…”
Section: Accuracymentioning
confidence: 99%
“…A series of studies [35][36][37] suggest CNN-based machine learning can be useful to detect malware, resulting in improved security. They say careful data preparation for training leads to an improvement in security.…”
Section: Security Of Aimentioning
confidence: 99%
“…Module. Build dynamic desensitization strategies by proxy for data analysis platforms such as enterprise unified business data centers, and ultimately achieve desensitization access to IT infrastructure resources [14,15]. If there is no new data resource or configuration requirement in the system, the desensitization method and task are stored in the desensitization access platform to prepare for subsequent call and execution.…”
Section: It Infrastructure Resource Desensitization Accessmentioning
confidence: 99%